p16ink4a Positivity of Melanocytes in Non-Segmental Vitiligo - Jin Wook Lee; Tae Hyung Kim; Tae Jun Park; Hee Young Kang (Diagnostics, 2020)
Cellular senescence is induced in response to cellular stressors such as increased levels of reactive oxygen species. The chronic accumulation of senescent cells is currently recognized as a contributor to the pathologic processes of diverse degenerative diseases. Vitiligo is characterized by the disappearance of melanocytes driven by cellular stress within melanocytes and autoimmune processes. In this study, we examined p16INK4A positivity in the lesional and perilesional skin of 54 non-segmental vitiligo patients to explore cellular senescence in vitiligo. There were more p16INK4A-positive melanocytes in the perilesional vitiligo skin samples than in control samples. It was also found that p16INK4A immunoreactivity was not restricted to melanocytes but also existed in fibroblasts; the number of p16INK4A-positive fibroblasts was significantly increased in lesional skin compared to perilesional skin and normal controls. However, in the subgroup analysis of sun-exposed and non-exposed samples, this outcome was only found at sun-exposed sites, suggesting that fibroblast senescence is an epiphenomenon related to the loss of pigment in skin with vitiligo. In summary, exploring p16INK4A positivity in vitiligo revealed melanocyte senescence in perilesional skin, which may play a role in vitiligo pathogenesis.